2020
DOI: 10.1021/acsaem.0c00410
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Ion Conducting UiO-66 Metal–Organic Framework Electrolyte for All-Solid-State Lithium Batteries

Abstract: A metal−organic framework (MOF) single lithium-ion conductor has been synthesized by covalently immobilizing anions to the skeleton of MOF structures. The functionalized UiO-66 MOF exhibits an electrochemical stability window of 5.2 V versus Li|Li + and ionic conductivity of 6.0 × 10 −5 , 7.9 × 10 −5 , and 1.1 × 10 −4 S/cm at 25, 60, and 90 °C, respectively. It displays single-ion conducting behavior with a high Li-ion transference number of 0.90 at 25 °C in the absence of any plasticizer. After ethylene carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 45 publications
1
56
0
Order By: Relevance
“…Over the past several decades, the successful application of lithium-ion batteries has revolutionized personal electronic devices and significantly changed our lifestyle [ 1 , 2 ]. All-solid-state lithium batteries (ASSBs) are promising battery systems for electric vehicles and smart devices owing to their safety, energy density, packaging, and operating temperature range compared with traditional liquid electrolytics [ 3 , 4 , 5 ]. However, the low ionic conductivity of solid electrolytes hinders their commercial applications [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, the successful application of lithium-ion batteries has revolutionized personal electronic devices and significantly changed our lifestyle [ 1 , 2 ]. All-solid-state lithium batteries (ASSBs) are promising battery systems for electric vehicles and smart devices owing to their safety, energy density, packaging, and operating temperature range compared with traditional liquid electrolytics [ 3 , 4 , 5 ]. However, the low ionic conductivity of solid electrolytes hinders their commercial applications [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Na-ion transference number (tNa+), proving the information of Na-ion mobility and diffusivity is a key parameter for QSS electrolytes. 40,260 It can be found that (Figure 6.13a, b) the tNa+ of the Celgard, PVDF-HFP, and hybrid QSS electrolytes are 0.18, 0.37, and 0.55, respectively. Higher tNa+ of the hybrid QSS electrolytes increasing with an increase of UiO-66 loading suggests the ability of activated UiO-66 that facilitates the Na-ion transport.…”
Section: Electrochemical Performance Of Uio-66@pvdf-hfp Separatorsmentioning
confidence: 99%
“…The activation energy (Ea) of the Na-ion migration in the QSS electrolytes was calculated using the slopes of ln (σ) vs. T -1 (Table 6 indicate a lower energy barrier for Na-ion migration, which is essential for the fabrication of polymer-based QSS electrolytes. 260 It has been established that the liquid electrolyte entrapped in the pores of the polymer matrix will further swell the amorphous domains to form a gel state. 276 Thus, Na-ions can be transferred in porous polymer-based QSS electrolytes: (a) through the liquid solution absorbed in pores; (b) through swelled amorphous domains; and (c) along molecular chains in the polymer matrix.…”
Section: Electrochemical Performance Of Uio-66@pvdf-hfp Separatorsmentioning
confidence: 99%
See 2 more Smart Citations